Analisis Pengembagan Usaha Ayam Petelur Terhadap Volume Produksi CV. Prian Di Desa Purwosari Kecamatan Natar Lampung Selatan - Saputra, Indra; Widodo, Deny Edy (Jurnal Manajemen DIVERSIFIKASI, 2022)
The prospect of laying hens business in Indonesia is considered very good in terms of domestic and foreign markets, when viewed from the supply and demand side. The laying hens business has good business prospects. This researcher aims to determine whether the amount of production is able to meet the market demand expected by CV.Prian Men. Based on the problems encountered, the purpose of this study is to provide empirical evidence in order to increase the amount of production in order to be able to meet market demand.The data used in this study are primary data and secondary data. Primary data can be obtained directly by interviewing business owners. And secondary data can be generated through data collection using the results of the financial test that has been done.Based on the analysis of CV Prian's laying hens production business in Purwosari Village, Natar District, South Lampung, what has been done can be concluded that it is economically feasible to do. With details Payback period (PP) Value (PP), Net Present Value (NPV) so that the business is economically feasible and profitable to realize. Furthermore, the value of the Internal Rate of Return (IRR) shows a feasible result to be developed,. Based on the results of research that has been carried out, it shows that the Laying Chicken Production Business owned by CV Prian in Purwosari Village, Natar District, South Lampung is quite good to be implemented, and has good prospects for development. Thus developing this business can meet the needs of eggs throughout Natar and outside the region.